PELATIHAN PEMBUATAN ALAT PERAGA MATEMATIKA BERBASIS PAIKEM GEMBROT UNTUK MENINGKATKAN PEMAHAMAN DAN MOTIVASI BELAJAR SISWA - Nurul Astuty Yensy; Teddy Alfra Siagian (Universitas Bengkulu, 2025)
One of the problems faced by the world of education is the weak learning process, so students are less active and creative, and learning tends to be boring. One learning model that can overcome this condition is PAIKEM GEMBROT (Active, Innovative, Creative, Effective, Fun, Joyful, and Weighted Learning). The initial survey showed that the knowledge of teachers of SD N 69 Kota Bengkulu was still low regarding the PAIKEM GEMBROT learning model, low understanding and motivation of students to learn in mathematics subjects, and the lack of availability of mathematics teaching aids that support the teaching and learning process so that learning is still abstract and challenging for students to understand, so that a Training Activity for Making Mathematics Teaching Aids Based on PAIKEM GEMBROT was carried out to improve Student Understanding and Motivation for Teachers of SD N 69 Kota Bengkulu. The activity method was in the form of workshops and seminars. The results of the training activities showed that the response of teachers of SD N 69 Kota Bengkulu was positive; all teachers had high motivation, and their knowledge of mathematics learning based on PAIKEM GEMBROT after being given training was in a suitable category as much as 100%. Keywords: PAIKEM GEMBROT, Mathematics teaching aids, Learning motivation